Assessing relationship between job stress, self efficacy and coping among teaching hospitals staff in Tabriz University of Medical sciences in 2009 - P Mehdizadeh; A Pourreza; H Allahverdipour; N Dopeykar (Tehran University of Medical Sciences, 2013)
Background: This study aimed to survey the relationship between job stress, self- efficiency and coping ability among staff of therapeutic- educational hospitals of Tabriz University of Medical sciences.Materials & Methods: This cross-sectional study was conducted in 2009 among therapeuticeducational hospitals of based on a two stage random sampling. Initially seven hospitals were selected using a simple random method and then 288 persons from the therapeutic and administrative staff were chosen as the sample to be studied using a classified random method. Data were collected using 4 questionnaires titled personal information, self-efficiency, Tores Theorell's job stress scale and Schwarzer's self efficacy and Coping Inventory for Stressful Situation CISS-21 ( Dutch's coping). Data were analyzed Using SPSS software version 11.5 and also Chi-Squared test, T -test, One-Way Anova , Regression analysis and Pearson correlation coefficient.Results: All the demographic variables including age, gender, marital status, working hours and work experience had a significant relationship with job stress. Pearson correlation test indicated a negative correlation between job stress and self- efficiency, working hours, age and work experience (P<0.001). Additionally there was a positive correlation between self- efficiency and working hours and age and coping ability with work experience ( p< 0.05).Conclusion: Considering the importance of staff`s mental health issue it is suggested that background factors such as high work load ,dignity level and social value and social supportive programs are taken into close consideration staff`s needs related to these issues are fully satisfied so that better health services are provided.